L'Îlot du palais de justice d'Épinal (Vosges) Formation et développement d'un espace urbain au Moyen Âge et à l'époque moderne - Henigfeld, Yves; Kuchler, Philippe (Documents d'archéologie française, 2014)
The work presents the results of two preventive excavations undertaken prior to the extension and reorganisation of the Palais de Justice at Épinal (Vosges), carried out in the late 1990s. These archaeological investigations covered a surface area of 3 000 m2, and were correlated with other documentary sources to provide new information on the origins of the town and the development of a quarter located at the heart of the urban space, between the château and the basilica of Saint-Maurice. The oldest traces of occupation of the sector date to the 8th-9th century, but it is only from the 10th century that the first redevelopments are attested, on the edges of a wet area on the site of a former watercourse. The space became gradually more structured between the 13th and early 17th centuries with the development of habitations opening onto rear courtyards and connected with artisanal and commercial activities. In the 1620s, the built environment was taken over by the Congrégation Notre-Dame. This religious order constructed a new convent in the 18th century. Following the Revolution, the religious buildings were employed for administrative functions before the construction in around 1820 of a prison, destroyed in the late 20th century. In addition to the information relating to the origins and transformation of the urban space, this publication offers an illuminating insight into the material and spiritual life of a district over a period of nearly a millennium. Finally, it provides an original view of the daily life of a religious community in the Modern period.